2008
DOI: 10.1080/15368370802061995
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency and Extremely Low-Frequency Electromagnetic Field Effects on the Blood-Brain Barrier

Abstract: During the last century, mankind has introduced electricity and during the very last decades, the microwaves of the modern communication society have spread a totally new entity--the radiofrequency fields--around the world. How does this affect biology on Earth? The mammalian brain is protected by the blood-brain barrier, which prevents harmful substances from reaching the brain tissue. There is evidence that exposure to electromagnetic fields at non thermal levels disrupts this barrier. In this review, the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 68 publications
0
28
0
1
Order By: Relevance
“…We have reviewed the literature since the 1970s examining the effects of EMF upon the BBB, studied both with albumin and other markers for leakage (Nittby et al 2008c). Here, we will only comment upon a few publications, in which albumin was used as marker, in attempts to replicate our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…We have reviewed the literature since the 1970s examining the effects of EMF upon the BBB, studied both with albumin and other markers for leakage (Nittby et al 2008c). Here, we will only comment upon a few publications, in which albumin was used as marker, in attempts to replicate our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that EMR from mobile phones affect neural function in humans although the studies contain conflicting reports and animal studies do not support the idea. Nittby et al (2008) reported that these effects range from changes in permeability of the blood-brain barrier to changes in EEG records pattern. However, recent papers reported that changes in permeability of the blood-brain barrier did not affect by 2.45 GHz and 1438 MHz EMR exposure (Cosquer et al 2005, Kuribayashi et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have shown dysfunction of the blood-brain barrier (BBB) caused by radiofrequency fields (25,26). Leakage of albumin into the brain has been demonstrated.…”
Section: Ci) --------------------------------------------------------mentioning
confidence: 99%